Effect of integrated Traditional Chinese and western medicine in the treatment of diabetic foot gangrene (中西医结合治疗糖尿病足坏疽临床效果观察) - CUI Yangfang (崔杨芳); ZHANG Xuejian (张雪键); LIU Ai (刘爱); TANG Yue (唐月); WANG Yanke (王艳可); ZHAO Yue (赵月) (Association of Integrative Nursing, 2021)
Objective To investigate the effect of integrated Traditional Chinese and western medicine in the treatment of diabetic foot gangrene. Methods Totally 60 patients with diabetic foot gangrene were randomly divided into the control group and observation group, with 30 cases in each group. Patients in the control group were treated by western medicine and nursing, and those in the observation group were given integrated Traditional Chinese and western medicine, which included Chinese herbal medicine internal and external application by syndrome differentiation. The treatment efficacy was evaluated and compared between two groups. Results The effective rate in observation group was higher than that in the control group (93. 33% vs. 70. 00%, P＜0. 05). Conclusion The integrated Traditional Chinese and western medicine is effective to relieve clinical symptom of patients with diabetic foot gangrene. (目的 探讨中西医结合治疗糖尿病足坏疽的临床效果。方法 60例糖尿病足坏疽患者随机分为对照组和观察组组, 各30例, 对照组采用常规西医治疗和护理, 观察组在对照组基础上进行中药内服和外用辨证干预。评估和对比2组干预效果。结果 观察组治疗有效率93. 33%(28/30), 高于对照组70. 00%(21/30), 差异有统计学意义(P＜0. 05)。结论 中西医结合治疗糖尿病足坏疽可以有效改善患者的临床症状。)